2022
DOI: 10.3390/tropicalmed7100293
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Monkeypox Concern and Risk among Men Who Have Sex with Men: Evidence and Perspectives from The Netherlands

Abstract: The current monkeypox epidemic is most prevalent among men who have sex with men (MSM). PrEP users and MSM with HIV (MSMHIV) are considered at highest risk of monkeypox infection in the Netherlands, and are being targeted for monkeypox vaccination. Together with the epidemiological evidence, perceived concern and risk are also relevant for decision making about health behaviour, e.g., vaccination uptake. It is thus timely to examine which subpopulations among MSM consider themselves to be most at risk and are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Few studies have focused the attention on the knowledge and attitudes about the mpox (19)(20)(21)(22)(23)(24)(25) notably among HCWs (26)(27)(28)(29). Identifying and understanding the knowledge and attitudes in this group is essential for the development of effective and strategic health communication.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have focused the attention on the knowledge and attitudes about the mpox (19)(20)(21)(22)(23)(24)(25) notably among HCWs (26)(27)(28)(29). Identifying and understanding the knowledge and attitudes in this group is essential for the development of effective and strategic health communication.…”
Section: Introductionmentioning
confidence: 99%
“…To date, very few studies have investigated the role of chemsex in the MPXV outbreak. Wang et al ( 123 ), showed that MSM using chemsex recently were less likely to perceive higher concern for MPXV infection ( 123 ). One of the explanations could be that MSM using chemsex tend to underestimate the STI risk in general ( 124 , 125 ).…”
Section: Resultsmentioning
confidence: 99%
“…It indicates that YMSM who had in‐person gathering activities in the past 6 months were more likely to feel a higher risk of mpox. A study in the Netherlands also found that MSM who had attended private sex parties had higher mpox risk perception 21 . It is understandable because it may have been commonly known that mpox virus is mainly transmitted through close contact among people in this outbreak, and in‐person gathering activities will highly possibly increase the risk of mpox infection 35 .…”
Section: Discussionmentioning
confidence: 96%
“…A study in the Netherlands also found that MSM who had attended private sex parties had higher mpox risk perception. 21 It is understandable because it may have been commonly known that mpox virus is mainly transmitted through close contact among people in this outbreak, and in-person gathering activities will highly possibly increase the risk of mpox infection. 35 The finding implies that messages about mpox risk behaviors should be an essential component in health education on mpox, and people with mpox risk behaviors should be placed a high priority in future mpox prevention and control in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation